Association of physical activity and sitting time with tobacco and alcohol use in 222,495 adolescents from 66 countries - Eduardo Rossato de Victo; Gerson Ferrari; Clemens Drenowatz; Dirceu Solé (BMC, 2024)
Abstract Background The prevalence of tobacco and alcohol use among adolescents is alarming, and these substances are among the leading risk factors for current and future health among adolescents. Physical activity has the potential to help prevent substance use among adolescents. The objective of this study was to evaluate the association between physical activity, modes of transportation to or from school, and sitting time with tobacco and alcohol use among 222,495 adolescents. Methods This cross-sectional study used data from national surveys conducted in 66 countries, obtained through the Global School-based Student Health Survey, and included adolescents aged 11 to 17 years. Information on physical activity, transportation to or from school, sitting time, and tobacco and alcohol use was collected through self-report questionnaires. Generalized linear models were employed to estimate the associations between these variables. Results The analysis, adjusted for sex, age, and region, revealed that being physically active was associated with lower odds of smoking (OR: 0.86, 95%CI: 0.83-0.89), alcohol use (OR: 0.74, 95%CI: 0.72-0.76), binge drinking (OR: 0.66, 95%CI: 0.62-0.69), and drunkenness (OR: 0.85, 95%CI: 0.83-0.88) compared to inactivity. Insufficiently active participants also had lower odds of tobacco use (OR: 0.83, 95%CI: 0.80-0.85), alcohol use (OR: 0.77, 95%CI: 0.75-0.79), binge drinking (OR: 0.91, 95%CI: 0.87-0.96), and drunkenness (OR: 0.88, 95%CI: 0.85-0.90) compared to inactive participants. Additionally, active transportation to or from school was associated with lower odds of tobacco use (OR: 0.97, 95%CI: 0.95-0.99), alcohol use (OR: 0.94, 95%CI: 0.92-0.96), and binge drinking (OR: 0.78, 95%CI: 0.75-0.81) compared to those using passive transportation. Participants with acceptable sitting time, however, were more likely to use tobacco (OR: 1.48, 95%CI: 1.45-1.52), use alcohol (OR: 1.68, 95%CI: 1.64-1.72), binge drink (OR: 1.68, 95%CI: 1.62-1.75), and experience drunkenness (OR: 1.66, 95%CI: 1.62-1.69) compared to those with excessive sitting time. Conclusion Being physically active, even at insufficient levels, may have beneficial effects on tobacco and alcohol use in adolescents. Acceptable sedentary time, on the other hand, was positively associated with tobacco and alcohol use.